2021
DOI: 10.3390/sym13122372
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory Ground Reaction Forces during Scoliotic Gait in Subjects with and without Right Adolescent Idiopathic Scoliosis

Abstract: Although the asymmetries of scoliotic gait in adolescent idiopathic scoliosis (AIS) groups have been extensively studied, recent studies indicated conflicting results regarding the ground reaction forces (GRFs) during gait in subjects with spinal deformity. The asymmetry during the stance phase might be clarified with three-dimensional (3D) compensations of GRFs between similar characteristics of subjects with and without AIS. The purpose of this study was to compare the normalized 3D GRF differences during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Subjects with AIS showed significantly reduced stance [ 52 , 53 ] and increased swing phases [ 52 , 54 ] compared to controls. Abnormalities in ground reaction forces (GRF) during gait were also reported: Bruynell et al [ 55 , 56 ] found stronger anteroposterior and vertical as well as weaker mediolateral impulses of the ground reaction forces during gait initiation in subjects with AIS, while Sung et al [ 57 ] found a greater mediolateral peak force in the dominant limb. Zhu et al [ 54 ] showed that the ratio of impulses between the big toe and the first metatarsal was greater in subjects with AIS than in healthy subjects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subjects with AIS showed significantly reduced stance [ 52 , 53 ] and increased swing phases [ 52 , 54 ] compared to controls. Abnormalities in ground reaction forces (GRF) during gait were also reported: Bruynell et al [ 55 , 56 ] found stronger anteroposterior and vertical as well as weaker mediolateral impulses of the ground reaction forces during gait initiation in subjects with AIS, while Sung et al [ 57 ] found a greater mediolateral peak force in the dominant limb. Zhu et al [ 54 ] showed that the ratio of impulses between the big toe and the first metatarsal was greater in subjects with AIS than in healthy subjects.…”
Section: Resultsmentioning
confidence: 99%
“…AIS did not seem to affect walking speed, stride length, and cadence of the subjects [ 21 , 52 , 60 ]. Subjects with AIS showed greater gait asymmetries [ 54 , 56 , 57 , 60 ], particularly in terms of GRF, step length, stance duration, and swing phases between the right and left feet. Yang et al [ 60 ] confirmed a generally lower correlation between left and right body segments (i.e., shank, thigh, pelvis, trunk) in the frontal and transverse planes in subjects with AIS compared to controls.…”
Section: Resultsmentioning
confidence: 99%
“…(Shumway-Cook & Woollacott, 2007;Pirker & Katzenschlager, 2017). Balance and posture of the body while standing and walking are essential to perform activities in daily life to prevent and minimize the risk of accidents that result in injury for all ages, possibly more for the older (Heglund, 1981;Beckham et al, 2014;Sung & Park, 2021;Shahabpoor & Pavic, 2017). Balance and the ability to bear weight play crucial roles in the well-being and quality of life of the elderly population.…”
Section: Introductionmentioning
confidence: 99%